2013
DOI: 10.1128/jvi.00925-13
|View full text |Cite
|
Sign up to set email alerts
|

UPF1 Is Crucial for the Infectivity of Human Immunodeficiency Virus Type 1 Progeny Virions

Abstract: The SF1 helicase MOV10 is an antiviral factor that is incorporated into human immunodeficiency virus type 1 (HIV-1) virions. We now report that HIV-1 virions also incorporate UPF1, which belongs to the same SF1 helicase subfamily as MOV10 and functions in the nonsense-mediated decay (NMD) pathway. Unlike ectopic MOV10, the overexpression of UPF1 does not impair the infectivity of HIV-1 progeny virions. However, UPF1 becomes a potent inhibitor of HIV-1 progeny virion infectivity when residues required for its h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
35
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(48 citation statements)
references
References 50 publications
3
35
0
Order By: Relevance
“…In this case, it is likely due to further alteration of nucleic acid configuration, leading to a block in reverse transcription. Our data complements a number of reports showing that the cellular proteins incorporated into the virions from producer cells can significantly alter the infectivity of the virions ((Serquiña et al, 2013), reviewed in Iordanskiy et al (2013)). MCM5 has the properties of an inhibitory factor that limits HIV-1 replication by interfering with production of an integration-competent cDNA product.…”
Section: Discussionsupporting
confidence: 86%
“…In this case, it is likely due to further alteration of nucleic acid configuration, leading to a block in reverse transcription. Our data complements a number of reports showing that the cellular proteins incorporated into the virions from producer cells can significantly alter the infectivity of the virions ((Serquiña et al, 2013), reviewed in Iordanskiy et al (2013)). MCM5 has the properties of an inhibitory factor that limits HIV-1 replication by interfering with production of an integration-competent cDNA product.…”
Section: Discussionsupporting
confidence: 86%
“…UPF1 is well known for its involvement in the NMD pathway (42) and was recently reported to restrict Semliki Forest virus infection. In contrast to restriction of viral replication, UPF1 is required for HIV1 virion production (47). In this study, we found that UPF1 is required for HCV replication (Fig.…”
Section: Discussionmentioning
confidence: 49%
“…Instead, using Rev‐deficient constructs, the authors recently showed that recruitment of UPF1 to these nuclear retained transcripts promotes their CRM1‐dependent export to the cytoplasm . UPF1 remains associated with HIV‐1 RNA in the cytoplasm and together with other cellular RNA‐binding proteins, UPF1 is packed into the HIV‐1 virions and was shown to be crucial for the infectivity of the virus . Available evidence suggests that UPF1 functions at the step of reverse transcription and that this function requires the helicase activity of UPF1, but the exact mechanism is not yet understood …”
Section: Biological Functions Of Nmdmentioning
confidence: 99%